2020
DOI: 10.1177/1076029620936772
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Acute Pulmonary Embolism in Patients With COVID-19 Associated Pneumonia From the City of Wuhan

Abstract: The aim of this study was to describe clinical, imaging, and laboratory features of acute pulmonary embolism (APE) in patients with COVID-19 associated pneumonia. Patients with COVID-19 associated pneumonia who underwent a computed tomography pulmonary artery (CTPA) scan for suspected APE were retrospectively studied. Laboratory data and CTPA images were collected. Imaging characteristics were analyzed descriptively. Laboratory data were analyzed and compared between patients with and without APE. A series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
57
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 32 publications
12
57
0
12
Order By: Relevance
“…The incidence of PE was 30% (73/242), similar to that reported by other recent studies [10,12,[28][29][30]. Three recent studies showed disparity results [31][32][33]. Of note, only 5/73 patients with PE had a confirmed diagnosis of deep vein thrombosis (DVT).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The incidence of PE was 30% (73/242), similar to that reported by other recent studies [10,12,[28][29][30]. Three recent studies showed disparity results [31][32][33]. Of note, only 5/73 patients with PE had a confirmed diagnosis of deep vein thrombosis (DVT).…”
Section: Discussionsupporting
confidence: 82%
“…In our sample, 96% (205/ 242) of the patients showed a DD value above normal limits (median 3260 ng/mL, [IQR 1203-9625]). Despite elevated DD levels in most patients, the PE-positive group showed higher values than the PE-negative group (7872 vs. 2009 ng/ mL, respectively, p < .001), similarly to other studies [28,[30][31][32][33]. Thus, DD along with other clinical and laboratory data can be used as a tool to effectively assess pre-CTPA PE risk in COVID-19 patients.…”
Section: Discussionsupporting
confidence: 76%
“…There are several manifestations of COVID-19 coagulopathy, such as deep venous thrombosis, pulmonary thromboembolism, and thrombotic microangiopathies. Out of 1008 patients with COVID-19, who underwent pulmonary CT-Angiography, Up to 40% of patients had small branches pulmonary thromboembolism [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Coagulopathy is one of the most concerning sequelae in COVID-19 patients. Several reports have shown mortality associated with pulmonary emboli and venous thrombosis in severely ill COVID-19 patients (192)(193)(194)(195)(196)(197)(198)(199). Interestingly, a study by Wichmann et al described the results of 12 mandatory autopsies of COVID-19, PCR confirmed patients.…”
Section: Comparison Of Cardiovascular Conditions Associated With Sarsmentioning
confidence: 99%